THE TAXPAYER’S NOTIFICATION OF THE NOTICE OF INFRACTION DEFINITIVELY CONSTITUTES THE TAX CREDIT AND STARTS THE LIMITATION PERIOD FOR ITS COLLECTION, PRECLUDING ANY DECADENTIAL TERM (CIPEEX, 2025)
This article distinguishes between the limitation period for assessment (decadential term) and the statute of limitations for collection, and argues that a valid notification of the notice of infraction definitively constitutes the tax credit and triggers the five-year limitation period for enforcement, leaving no room for decadence after assessment. The objective is to describe the steps required to constitute the credit and to assess, in light of technological advances in tax administration, whether current statutory time limits remain adequate. The study employs a doctrinal approach based on bibliographic research and an examination of administrative routines and electronic audit systems, showing how automated data-matching and digitized ancillary obligations have accelerated assessments. The findings indicate that credit constitution generally occurs more swiftly than when the legal deadlines were enacted, which supports the view that, once the taxpayer is notified of the notice of infraction, only the five-year statute of limitations governs collectability. The conclusion is that fixing the limitation term’s dies a quo at the notification stage enhances predictability, and that legislative recalibration of both assessment and collection time limits—aligned with technological realities and legal-certainty safeguards—can reduce uncertainty, opportunistic litigation, and asymmetries between the tax authority and taxpayers.
Keywords: tax assessment; notice of infraction; statute of limitations; assessment limitation period (decadential term)